2012
DOI: 10.1038/nature11209
|View full text |Cite
|
Sign up to set email alerts
|

A framework for human microbiome research

Abstract: A variety of microbial communities and their genes (microbiome) exist throughout the human body, playing fundamental roles in human health and disease. The NIH funded Human Microbiome Project (HMP) Consortium has established a population-scale framework which catalyzed significant development of metagenomic protocols resulting in a broad range of quality-controlled resources and data including standardized methods for creating, processing and interpreting distinct types of high-throughput metagenomic data avai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
1,241
2
17

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 2,262 publications
(1,305 citation statements)
references
References 21 publications
18
1,241
2
17
Order By: Relevance
“…However, the eubacterial:human ratios were compromised for the fecal metagenomic DNA isolated using commercial methods (2 13 :1 for method A, 2 12 :1 for method B, and 2 0.143 :1 for method C, 2 20.8 :1 for method D). Similar observation on host genomic DNA contamination in fecal metagenomic DNA was recorded during the HMP study using method A [6].…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…However, the eubacterial:human ratios were compromised for the fecal metagenomic DNA isolated using commercial methods (2 13 :1 for method A, 2 12 :1 for method B, and 2 0.143 :1 for method C, 2 20.8 :1 for method D). Similar observation on host genomic DNA contamination in fecal metagenomic DNA was recorded during the HMP study using method A [6].…”
Section: Resultssupporting
confidence: 81%
“…The total number of microbes residing in the human body, especially in the gut, outnumbers that of human cells [3]. A vast array of recent studies has identified many microbial enterotypes in the human gut [4], [5], [6], [7], [8], [9], [10] and their potential roles in immunity [5], [7], [8], development [8], digestion [9], and other functions [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This pipeline was applied in the Human Microbiome Project [25]. The sequences were separated using the sample-specific ‘barcodes’.…”
Section: Methodsmentioning
confidence: 99%
“…Environmental samples were sent to and analysed by GATC Biotech AG (Konstanz, Germany). The microbial community was established by amplicon sequencing of a 570 bp (excluding primer length) fragment of the V3‐V5 hypervariable region 17. PCR amplification was performed by using the 357F (CCTACGGGAGGCAGCAG) and 926R primer (CCGTCAATTCMTTTRAGT).…”
Section: Methodsmentioning
confidence: 99%